Recent Progresses in Plasmonic Biosensors for Point-of-Care (POC) Devices: A Critical Review - Caterina Serafinelli; Alessandro Fantoni; Elisabete C. B. A. Alegria; Manuela Vieira (Chemosensors, 2023)
The recent progresses in the research of plasmonic phenomena and materials paved the route toward the development of optical sensing platforms based on metal nanostructures with a great potential to be integrated into point-of-care (POC) devices for the next generation of sensing platforms, thus enabling real-time, highly sensitive and accurate diagnostics. In this review, firstly, the optical properties of plasmonic metal nanoparticles will be illustrated, whereafter the engineering of POC platforms, such as microfluidics and readout systems, will be considered with another critical point which is surface functionalization. Attention will also be given to their potential in multiplexed analysis. Finally, the limitations for effective implementation in real diagnostics will be illustrated with a special emphasis on the latest trend in developing cutting-edge sensing systems.